The Meaning of Education for Children of Orange Farmers in Sambimulyo Banyuwangi: A Status Reorientation - Setiawan, Hafid Kuncoro; Kusumah, Maulana Surya (Jurnal ENTITAS SOSIOLOGI, 2018)
Citrus fruit farming in Sambimulyo Village has succeeded in improving the welfare of local farmers. Their success did not make them think of sharing their knowledge of citrus fruit farming to their children. They choose the education field as an appropriate way for their children. Citrus fruit farmers thought that education as the critical point to get knowledge and job and also an important thing to create a better future. The same thought also had by the citrus fruit farmer's children. This research used a qualitative method by the descriptive research design. The rational theory of James Coleman chooses as the theory in the preferential mind and optimization process; thereby, it explained the development of mind mapping and rational action, which is selected by the farmer. The research question is how the status reorientation as the meaning of education to citrus fruit farmer's children in Sambimulyo Banyuwangi. The researcher identifies the concept of knowledge and the implementation of it. Moreover, how the citrus fruit farmer faced the direct impact from the orientation of education primarily related to citrus fruit agricultural in Sambimulyo. It implemented on differing views between the old generation and the young generation. The difference is in how they used the education itself, and the same is in the way to get knowledge and a better life. Keywords: status reorientation, the meaning of education, rational choice, orange farmer. Referensi: Ahmadi dan Uhbiyati. 2007. Ilmu Pendidikan. Jakarta: PT Rineka Cipta. Buku Profil Desa Sambimulyo Tahun 2011 – 2015. Bungin, Burhan, 2001. Analisis Data Penelitian Kulaitatif: Pemahaman Filosofis dan Metodologis ke Arah Penguasaan Model Aplikasi. Jakarta: PT. Raja Grafindo Persada. Coleman, James. 1994. Dasar-dasar Teori Sosial (Foundations Of Social Theory). Terjemahan oleh Imam Muttaqien, Derta Sri Widowatie, Siwi Purwandari. 2011. Bandung: Nusa Media. Creswell, Jhon W. 2016. Research Design “Pendekatan Metode Kualitatif, Kuantitatif, dan Campuran. Terjemahan oleh Achmad Fawaid dan Rianayati Kusmini Pancasari. 2016. Yogyakarta: Pustaka Belajar Miles, Matthew dan Huberman, A. Michael. 1992. Analisis Data Kualitatif: Buku Sumber Tantang Metode-Metode Baru. Terjemahan oleh Tjetjep Rohendi Rohidi. 2009. Jakarta: UI Press. Notoatmodjo, Soekidjo. 2003. Pendidikan dan Perilaku Kesehatan. Jakarta: Rineka Cipta I.B Wirawan, Teori-Teori Sosial Dalam Tiga Paradigma (Fakta Sosial, Definisi Sosial, Perilaku Sosial), 2012, Jakarta: Kencana Prenada Media Group. Alhadi, Robith Abdillah. 2015. Sejarah Pertanian Jeruk di Desa Sambimulyo Kecamatan Bangorejo Kabupaten Banyuwangi. Jurnal : Universitas Jember. (Skripsi tidak diterbitkan)